Bladder Paraganglioma: Clinicopathology and Magnetic Resonance Imaging Study of Five Patients - Liang, Jiuping; Li, Hengguo; Gao, Likun; Yin, Liang; Yin, Lei; Zhang, Jiawen (Urology Journal, 2016)
Purpose: To investigate the clinicopathology and magnetic resonance imaging (MRI) features of bladder paraganglioma, an extremely rare clinical entity. Materials and Methods: Five patients with bladder paraganglioma (3 males and 2 females, 27-52 years old) were retrospectively reviewed. All cases underwent baseline MRI and contrast-enhanced scans, and three cases underwent diffusion weighted imaging (DWI) and cystoscopy. Cases were immunohistochemically examined with neuroendocrine markers (chromogranin and synaptophysin) and Ki-67, and histology was reviewed by a pathologist. Results: Three cases exhibited painless gross hematuria, including one case with hypertension, whereas two cases were asymptomatic. One of the three patients who underwent cystoscopy was negative. The tumors were round (n = 1) or oval (n = 4) and located in the anterior wall (n = 1), posterior wall (n = 1), lateral wall (n = 2) or trigone (n = 1). All tumors were located in the submucosal or lamina propria. Four cases presented with well-circumscribed margins, whereas one case was poorly circumscribed. All tumors exhibited slight hyperintensity on T1-weighted images (T1WI) and hyperintensity with "salt and pepper" appearance on T2-weighted images (T2WI). DWI indicated strong hyperintensity, and all cases exhibited conspicuous enhancement after intravenous gadobenate dimeglumine (Gd-DTPA) injection. Pathological evaluation confirmed paraganglioma. Conclusion: MRI plays an important role in the preoperative diagnosis of bladder paraganglioma. This rare condition has a characteristic round or oval appearance, located in the submucosal area, with slight hyperintensity on T1WI and hyperintensity with "salt and pepper" appearance on T2WI. DWI indicated strong hyperintensity and conspicuous enhancement on contrast-enhanced scans.